2017
DOI: 10.1155/2017/8219841
|View full text |Cite
|
Sign up to set email alerts
|

Sporotrichoid-Like Spread of Cutaneous Mycobacterium chelonae in an Immunocompromised Patient

Abstract: Mycobacterium chelonae is a rapidly growing mycobacterium found in water and soil that can cause local cutaneous infections in immunocompetent hosts but more frequently affects immunocompromised patients. Typically, patients will present with painful subcutaneous nodules of the joints or soft tissues from traumatic inoculation. However, exhibiting a sporotrichoid-like pattern of these nodules is uncommon. Herein, we report a case of sporotrichoid-like distribution of cutaneous Mycobacterium chelonae in a patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
6
0
2
Order By: Relevance
“…We entertained the diagnosis of a naturally evolving and relapsing M chelonae infection for many months, because the patient adhered reliably to therapy, endured adverse effects, presented with a seemingly sporotrichoid pattern of progression well described for M chelonae infections [ 7 ], and experienced apparently treatment-related emergence of a rrl gene mutation conferring clarithromycin resistance ( Supplementary Data ). Because difficult-to-treat M chelonae infections are primarily encountered in immunocompromised patients [ 8 ], we even planned a diagnostic work-up for genetic Mendelian susceptibility to mycobacterial disease [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…We entertained the diagnosis of a naturally evolving and relapsing M chelonae infection for many months, because the patient adhered reliably to therapy, endured adverse effects, presented with a seemingly sporotrichoid pattern of progression well described for M chelonae infections [ 7 ], and experienced apparently treatment-related emergence of a rrl gene mutation conferring clarithromycin resistance ( Supplementary Data ). Because difficult-to-treat M chelonae infections are primarily encountered in immunocompromised patients [ 8 ], we even planned a diagnostic work-up for genetic Mendelian susceptibility to mycobacterial disease [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Skin lesions may appear as erythematous or violaceous papules or plaques, pustules, folliculitis, or panniculitis (1-3, 5, 6). In rare cases, the infection may also present with a "sporotrichoid" pattern, spreading along subcutaneous lymphatics from the site of entry (32). Later on, skin lesions can become erosive or ulcerated (1-3, 5, 6).…”
Section: Discussionmentioning
confidence: 99%
“…In a review of the literature (1987–2017, conducted through PubMed), we identified 14 2,3,1022 cases of cutaneous M. chelonae infection presenting with a sporotrichoid pattern of spread. The vast majority of these cases (80%; 11/14) occurred in immunocompromised patients.…”
Section: Discussionmentioning
confidence: 99%